Guidance and Counseling Teacher Strategies in Overcoming Student Discipline Problems at SMA Muhammadiyah 1 Medan - Sarah, Sarah (Indonesian Journal Education, 2023)
This study aims to investigate the role of Guidance and Counseling teachers in overcoming the problem of student tardiness at SMA Muhammidiyah 1 Medan. The results of the study show that Guidance and Counseling teachers play a role in providing guidance, direction, and individual counseling to students who come late to school. The reasons for being late for students vary, such as difficulty getting up early, tired of helping parents after school, or a lack of interest in math. The provision of individual counseling services by Guidance and Counseling teachers has succeeded in showing a decrease in cases of students arriving late to school. Thus, the application of individual counseling services can be a solution in overcoming the problem of student delays at SMA Muhammadiyah 1 Medan.